Techniques, indications and complications of pericardiocentesis - Elkahwagy, Mohammed Shafik; Alenezi, Ahmad Faraj; Alenezi, Hibah Farhan; Al-Hussain, Bader Naji; Allwaim, Mohammad Ahmad; Almomatten, Almukhtar Mohammed; Alkhuwaysah, Mohammed Ali; Alwabari, Mohammed Abdullah; Alarabi, Thumamah Mahmoud; Albarakati, Mohammed Hamed; Albadrani, Naif Abdullah; Alrehaili, Nasser Dakhel (International Journal Of Community Medicine And Public Health, 2021)
The main aim of pericardiocentesis is to remove excess fluid in the pericardial space and enhance the functions of the heart to intervene against the development of many complications. Accordingly, the procedure is usually performed to manage cardiac tamponade to correct secondary hypotension that attributes to the low stroke volume as a result of the external pressure of the pericardial fluid on the chambers of the heart. In the present literature review, we have discussed the techniques, indications, and complications of pericardiocentesis. Furthermore, the main techniques and approaches include computed tomography-guided pericardiocentesis, echo-guided, and fluoroscopy-guided techniques. These modalities can be successfully used for hemodynamically unstable patients to adequately remove excess fluid to normalize ventricular filling and maintain adequate cardiac output to the peripheral tissues. Considerations for using the modality have been made for small effusions and many authors suggest that it should not be routinely used in these situations. Many major and minor complications can occur secondary to conducting pericardiocentesis. The major complications might include lacerations of the intercostal vessels of the coronary arteries, injury to the cardiac chambers, death, puncture of the peritoneal cavity or abdominal viscera, pneumopericardium, pneumothorax which might require chest intubation, pericardial decompression syndrome, and ventricular arrhythmias. Therefore, carefully approaching these patients and deciding the best management plan, in addition to providing proper interventional approaches for the potential development of these complications is essential to enhance the intended outcomes and enhance the quality of care.